Pequeñas percepciones e Ilustración en Leibniz y Kant. Una revisión de la intepretación deleuziana de Leibniz - Sánchez Rodríguez, Manuel (2014)
In this paper we focus on Deleuze’s interpretation of small perceptions in Leibniz’s thought, as well as on the supposed abandon of this notion in Kant. In connection with the two issues we contend that the way both authors deal with them makes sense within the framework of the Enlightenment.